Easy One-Pot Low-Temperature Synthesized Ag-ZnO Nanoparticles and Their Activity Against Clinical Isolates of Methicillin-Resistant Staphylococcus aureus - Naskar, Atanu; Lee, Sohee; Kim, Kwang-sun (Frontiers in Bioengineering and Biotechnology, 2020)
Antimicrobial resistance (AMR) is widely acknowledged as a global health problem, yet the available solutions to this problem are limited. Nanomaterials can be used as potential nanoweapons to fight against this problem. In this study, we report an easy one-pot low-temperature synthesis of Ag-ZnO nanoparticles (AZO NPs) and their targeted antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA) strains. The physical properties of the samples were characterized by X-ray diffractometry (XRD), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Furthermore, minimum inhibitory concentration (MIC), zone of inhibition (ZOI), and scanning electron microscopy (SEM) images for morphological characterization of bacteria were assessed to evaluate the antibacterial activity of AZO NPs against both gram-negative (Escherichia coli [E. coli] and Acinetobacter baumannii [A. baumannii] standard and AMR strains) and gram-positive (Staphylococcus aureus [S. aureus], MRSA3, and MRSA6) bacteria. The AZO NPs showed comparatively better antibacterial activity against S. aureus and MRSA strains than gram-negative bacterial strains. This cost-effective and simple synthesis strategy can be used for the development of other metal oxide nanoparticles, and the synthesized nanomaterials can be potentially used to fight against MRSA.